Seismic wavefield sampling : a wave number approach to acquisition fundamentals - Vermeer, Gijs J. O. (Geophysical references ;, 1990)
This book discusses a number of subjects concerning seismic data acquisition and seismic data processing. The author explains how the description of multiple-coverage data, gathered for a 2-D seismic line, as a three-dimensional wavefield is of prime importance to a proper understanding of seismic data acquisition and intimately related seismic data processing problems.